Psychosocial impact of acne scarring: correlational study at Euderma Clinic Bali - Sari, Ida Ayu Diah Purnama; Purnamayanti, Ni Kadek Diah (Universitas Gadjah Mada, 2023)
Purpose: Acne scars are abnormalities in the contour and color of the skin that occur due to acne vulgaris, caused by increased tissue formation or local tissue damage and loss, which often causes disability, especially on the face. Acne scars often cause aesthetic, psychological, social, and emotional problems. This is a challenge for doctors to carry out comprehensive treatment strategies including primary, secondary, and tertiary prevention efforts. This research aims to determine the correlation between psychosocial impact and acne scars at the Euderma Clinic. Methods: The research method used was descriptive cross-sectional. The sampling technique used consecutive sampling, namely collecting participants who underwent acne scar management at the Euderma Clinic in the period May-July 2023. In this study, data collection was carried out using a questionnaire that included patient characteristics, acne history, and description of acne scars. The data was analyzed descriptively and correlatively for further data interpretation. Results: Descriptive test results on 121 samples, mostly female (77.7%), mature (72.7%), had a history of untreated acne for > 12 months, (46.3%), and had a habit of squeezing. acne (53.7%), and the severity of acne pustules > 20 (51.9%). The appearance of acne scars is mostly mild (40.5%) and moderate (39.7%). The correlation test results show a close relationship between acne scars and psychosocial impacts. Conclusion: The severity of acne scars in adults is mostly at the mild to moderate stage. Prevention efforts that can be taken are to carry out appropriate acne treatment so that inflammation does not prolong. Management of mild moderate acne scars can be done with laser procedures and subcision to increase patient confidence.